Understanding and using English grammar interactive - Azar, Betty Schrampfer; Koch, Spack Rachel ([New York] : Pearson Longman, 2005)
This cd-rom combines the best instruction and practice in one program includes lively grammar presentations, extensive grammar practice, learner support and ongoing assessment
Guide to use this CD: 1. Need pc that connected with Internet. 2. Install the program by follow the instruction given. 3. Click the icon at the desktop to use this program
Single user version
Being installed at user's PC 1 Bahagian Koleksi Media
System requirements: Windows 98, XP, 2000 with Service Pack 2 (or higher), or NT 4.0 with Service Pack 5 (or higher). Non-English Windows 2000 systems require the Professional edition. Pentium II processor 400+ MHz ; 128+ MB RAM (256 MB recommended) ; 16-bit graphics card ; monitor resolution of 800 X 600 or higher ; sound card, microphone, and speakers (microphones plugged into USB ports are not supported) ; 10X CD-ROM drive ; floppy disc drive (for saving student data) ; Internet Explorer 5.0 or higher (5.5 or higher recommended). NOTE: Netscape and AOL browser software are not supported. Macromedia's Flash 6 (or higher) and Shockwave 8 (or higher) (Apple's QuickTime 6.5 (or higher), and Sun's Java 1.4.1-01 plug-ins). NOTE: If computer does not have these plug-ins, they will be installed automatically when course is installed. Adobe Acrobat Reader 4.0 (or higher) software
Keywords: English language -- Grammar -- Problems, exercises, etc. -- Interactive multimedia; English language -- Textbooks for foreign speakers